Sharia economic legal perspective on the practices of the savings and loan units of Harapan Mandiri Village in Talang Tinggi Village Seluma West Bengkulu District - Tio Saputra (Requisitoire Law Enforcement, 2023)
Sharia Economic Law Perspective on Savings Unit Practices Borrowed from BUMDes Harapan Mandiri in Talang Tinggi Village, Seluma District. There are two issues studied in this thesis, namely: (1). How the Harapan Mandiri Village-Owned Enterprise Savings and Loan Unit (BUMDES) Practices in Talang Tinggi Village, West Seluma District, Bengkulu. (2). How is Sharia Economic Law Perspective for the Practical Solution for the Harapan Mandiri Village-Owned Enterprise Savings and Loans Business Unit (BUMDES) in Talang Tinggi Village, West Seluma District, Bengkulu in accordance with Sharia Economic Law. To reveal this problem in depth and comprehensively, researchers used qualitative methods which are useful for providing information, facts, data and mechanisms regarding the practice of savings and loan units in Talang Tinggi Village, West Seluma District, Bengkulu. From the results of this research, it was found that (1) In the practices carried out by the Harapan Mandiri BUMDes Savings and Loans Unit, there were transactions that were detrimental to one party because there was no guarantee in the event of bad credit (2) The practices carried out by the Harapan Mandiri Savings and Loans Unit were not in accordance with the law. Sharia Economics. Because the transaction contains usury, namely usury qard or taking benefits. The aim of the research is to determine the efficiency of the business by looking at the benefits it provides to the local community's economy, developing Village funds to become a driver of economic activity for the residents of Talang Tinggi Village, encouraging creative small businesses and household businesses to develop with the support of capital financing, increasing Income Revenue. Asli Desa through BUMDes Business activities, improving the welfare of village communities by involving the community in BUMDes business unit activities through collaboration business.